1994
DOI: 10.1002/qua.560490316
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on metal NMR chemical shifts: Germanium compounds

Abstract: Germanium chemical shifts were studied theoretically by the ab initio molecular orbital method. The compounds studied were GeMe4-,CI, and GeMe4-,Hx(x = 0-4). The calculated values of the germanium chemical shifts agreed well with the available experimental values. The germanium chemical shift is due to the p-electron mechanism that reflects the ligand electronic effect on the p -p ' excitation term in the second-order paramagnetic term. For GeMed-,H,, the chemical shift is almost linear to the number of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…We have investigated the mechanism of the chemical shifts for a variety of metal complexes and found that the primary mechanism of the chemical shift is an intrinsic property of the central resonant metal atom itself and therefore can be understood from the position of the element on the periodic table. [132][133][134][135][136][137][138][139][140][141][142] However, this is not the case when we examine the chemical shift induced by the halogen ligands. We have two different dependences: normal halogen dependence and inverse halogen dependence.…”
Section: Relativistic Quantum Chemistry and The Electronic Theory Of mentioning
confidence: 99%
“…We have investigated the mechanism of the chemical shifts for a variety of metal complexes and found that the primary mechanism of the chemical shift is an intrinsic property of the central resonant metal atom itself and therefore can be understood from the position of the element on the periodic table. [132][133][134][135][136][137][138][139][140][141][142] However, this is not the case when we examine the chemical shift induced by the halogen ligands. We have two different dependences: normal halogen dependence and inverse halogen dependence.…”
Section: Relativistic Quantum Chemistry and The Electronic Theory Of mentioning
confidence: 99%